Prevalence of Germline Alterations on Targeted Tumor-Normal Sequencing of Esophagogastric Cancer - Ku, Geoffrey Y; Kemel, Yelena; Maron, Steve B; Chou, Joanne F; Ravichandran, Vignesh; Shameer, Zarina; Maio, Anna; Won, Elizabeth S; Kelsen, David P; Ilson, David H; Capanu, Marinela; Strong, Vivian E; et al. (JAMA Network Open, 2021)
IMPORTANCE: Among patients with esophagogastric cancers, only individuals who present with known features of heritable cancer syndromes are referred for genetic testing. Broader testing might identify additional patients with germline alterations. OBJECTIVES: To examine the prevalence of likely pathogenic or pathogenic (LP/P) germline alterations among patients with esophagogastric cancer and to assess associations between germline variant prevalence and demographic and clinicopathologic features. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study was performed at a tertiary referral cancer center from January 1, 2014, to December 31, 2019, in 515 patients with esophagogastric cancer who consented to tumor and blood sequencing. MAIN OUTCOMES AND MEASURES: Presence or absence of LP/P variants in up to 88 genes associated with cancer predisposition syndromes as identified by targeted sequencing (Memorial Sloan Kettering–Integrated Mutation Profiling of Actionable Cancer Targets). RESULTS: Among 515 patients (median age, 59 years; range, 18-87 years; 368 [71.5%] male; 398 [77.3%] White), 243 (47.2%) had gastric cancer, 111 (21.6%) had gastroesophageal junction (GEJ) cancer, and 161 (31.3%) had esophageal cancer. A total of 48 patients with gastric cancer (19.8%), 16 (14.4%) with GEJ cancer, and 17 (10.6%) with esophageal cancer had LP/P germline variants. The number of LP/P variants in high- and moderate-penetrance genes was significantly higher in patients with gastric cancer (29 [11.9%]; 95% CI, 8.1%-16.7%) vs patients with esophageal cancer (8 [5.0%]; 95% CI, 2.2%-9.6%; P = .03), and the difference was greater for high-penetrance germline alterations in patients with gastric cancer (25 [10.3%]; 95% CI, 6.8%-14.8%) vs in patients with esophageal cancer (3 [1.9%]; 95% CI, 0.38%-5.3%; P = .001). The most frequent high- and moderate-penetrance LP/P alterations were in BRCA1/2 (14 [2.7%]), ATM (11 [2.1%]), CDH1 (6 [1.2%]), and MSH2 (4 [0.8%]). Those with early-onset disease (≤50 years of age at diagnosis) were more likely to harbor an LP/P germline variant (29 [21.0%]; 95% CI, 14.5%-28.8%) vs those with late-onset disease (patients >50 years of age at diagnosis) (52 [13.8%]; 95% CI, 10.5%-17.7%; P = .046). ATM LP/P variants occurred in 6 patients (4.3%; 95% CI, 1.6%-9.1%) with early-onset esophagogastric cancer vs 5 (1.3%; 95% CI, 0.4%-3.1%; P = .08) of those with late-onset esophagogastric cancer. CONCLUSIONS AND RELEVANCE: These results suggest that pathogenic germline variants are enriched in gastric and early-onset esophagogastric cancer and that germline testing should be considered in these populations. The role of ATM alterations in esophagogastric cancer risk warrants further investigation.